Beyond Capture: Circulating Tumor Cell Release and Single‐Cell Analysis. Issue 5 (14th February 2019) - Wu, Lingling; Xu, Xing; Sharma, Bineet; Wang, Wei; Qu, Xin; Zhu, Lin; Zhang, Huimin; Song, Yanling; Yang, Chaoyong
Abstract: As the most promising "liquid biopsy", analysis of circulating tumor cells (CTCs) provides noninvasive access to obtain biological information of solid tumors. It not only advances the understanding of the mechanisms underlying tumor metastasis, relapse, and chemoresistance, but also promotes the development of precision medicine. Over the past decade, the rapid advances in micro/nanomaterials and microfluidics have overcome the technical challenges of capturing CTCs, allowing efficient enrichment and sensitive detection. Beyond the capture of CTCs, major challenges of in‐depth CTC analysis are the release of CTCs from capture platforms and the inherent heterogeneity in CTCs. A variety of technologies have now emerged for release and single‐cell analysis of CTCs. This review focuses on recent progress along this direction. First, different release strategies are outlined and discussed, including their design principles and characteristics (merits and limitations). Then, existing methods for single CTC analysis at the genomic, transcriptomic, proteomic, and functional level are summarized. Finally, some perspectives are provided on current development trends, future research directions, and challenges of CTC studies. Abstract : Release and single‐cell analysis of circulating tumor cells (CTCs) has gained increasing attention due to their significance in tumor biology studies and personalized therapy. In this review, different CTC release strategies, including bulk release and single‐cell release, are diccussed, and single CTC analysis platforms at the genomic, transcriptomic, proteomic, and functional level are summarized.